Clinical analysis and case series report on autoimmune glial fibrillary acidic protein astrocytopathy presenting with autonomic dysfunction - Xiao Ke Wu; Guojie Zhai; Jin Ru Zhang; Hua Ping Du; Lan Hu; Shu Ye Yu; Hai Lun Hang; Sirui Han; Yanlin Zhang; Yuan Xu (Frontiers in Neurology)
Background and purposeThe incidence of autonomic dysfunction is frequently underestimated and often overlooked in patients with autoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A). This study comprehensively analyzes the clinical manifestations, laboratory and imaging findings, and treatment modalities for patients demonstrating GFAP-A involvement in the autonomic nervous system. The present article primarily elucidates the prevalence and prognosis of diverse autonomic system symptoms while examining the associated laboratory and imaging indicators. These findings aim to establish a foundation for personalized diagnosis and treatment strategies in such patients.MethodWe performed a retrospective data analysis from three cases of GFAP-A involvement in autonomic nerves from the Ninth People’s Hospital of Suzhou and the Second Affiliated Hospital of Soochow University from 2020 to 2023. After an extensive literature review, we identified 39 cases involving GFAP-A and autonomic nervous system dysfunction. We also comprehensively analyzed the patient’s clinical manifestations, laboratory biomarkers, and imaging findings.ResultThe study included a total of 42 patients, consisting of 15 females and 27 males. The primary manifestations of autonomic dysfunction included bladder dysfunction (41/42 cases), gastrointestinal dysfunction (18 /42 cases), heart rate variability (4/42 cases), unusual sweating (2/42 cases), and blood pressure fluctuations (1/42 cases). Other neurological symptoms comprised headache (12 /42 cases), limb weakness presentation (30/42 cases). Blood pressure variability is related to cerebrospinal fluid pressure and convulsive seizures. Heart rate variability is related to disorders of consciousness. unusual sweating was associated to age, gender, cerebrospinal fluid protein content and convulsive seizures. Gastrointestinal disorders have associations with gender, sleep disturbances, protein content in the cerebrospinal fluid, and brain MRI lesions. The prognosis of autonomic nerve dysfunction is associated to sleep disorder and cerebrospinal fluid protein content. The higher the cerebrospinal fluid protein level, the worse the prognosis of autonomic nervous system.ConclusionBladder dysfunction and gastrointestinal dysfunction are the primary manifestations of autonomic dysfunction in GFAP-A patients, with a subset also experiencing abnormalities in heart rate, blood pressure, and sweating. These additional symptoms have implications for prognosis, necessitating heightened attention from clinicians toward GFAP-A patients.